Atypical proliferative Brenner tumour of the ovary with liver metastases: a case report - Vali, Saaliha; Oumar, Mohamed; Chavhan, Shefali; Wise, Olga; Sayasneh, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Brenners tumours constitute up to 2% of ovarian neoplasms. Most are benign with a gross fibroma like appearance. Here we present the case of a 45 year old woman who underwent a full staging laparotomy for a suspicious left ovarian mass. A 30 cm left ovarian cyst was found with no enlarged lymph nodes. Histologically this was a proliferative Brenner tumour. Postoperatively, a mild increase in the Ca125 prompted an MRI scan which revealed a 3 cm liver cyst. This was resected and histologically found to be a transitional cell carcinoma. Successful treatment with secondary excision and adjuvant chemotherapy has ensured disease free remission to date.